Antiresorptive medication-related osteonecrosis of the jaw: Incidence and preventive measures utilization in cancer patients - Salman Ali Alabdali; Abdulrahman Ali Alabdali; Sultan Qais Alnoaman; Abdullah Abuasida; Saud Balelah; Abdulaziz Almuzaini; Abdullah Homeed Almatrafi; Hossein M. Elbadawy (Saudi Dental Journal)
Introduction: Antiresorptive drugs are commonly used to treat cancer and bone metastases. These drugs can impose the risk of osteonecrosis of the jaw (ONJ). ONJ is a serious complication that can lead to significant morbidity and mortality. This study aimed to investigate the incidence and preventive measures utilization of ONJ among cancer patients treated with antiresorptive agent. Materials and Methods: This retrospective cohort study investigated 210 adult patients with cancer on either zoledronic acid (ZA) or denosumab at a tertiary cancer center. The primary endpoint was to determine the incidence rate of Osteonecrosis of the Jaw. Secondary endpoints were to determine the utilization rate of antiresorptive agent related ONJ preventive measures and the exposure duration of antiresorptive agents to the ONJ incidence. Results: Of 210 patients, 68 were on zoledronic acid (group 1) and 142 were maintained on denosumab (group 2). The median incidence rate of medication related ONJ (MRONJ) was 3.8 % (8 out of 210), with 4.4 % (3 out of 68) in the first group and 3.5 % (5 out of 142) in the second group. All ONJ cases were females with metastatic breast cancer to bone. The utilization rate of ONJ preventive measures was 5.2 %, including regular dental check-ups (3.3 %) and oral hygiene education (1.9 %). The median duration of exposure before ONJ was 1 year for zoledronic acid and 2 years for denosumab. Risk factors included female sex, diabetes mellitus, and hypertension. Duration of Denosumab exposure, but not ZA, was associated with incidence of ONJ. Conclusion: Higher incidence rate of ONJ among denosumab-treated group. The findings emphasize the importance of female sex, diabetes, and hypertension as significant risk factors. The use of preventive measures was found to be low, indicating a need for better education and awareness.